Qirāʼah fī Tajribat al-Maṭbaʻah al-Sulṭānīyah fī Zanjibār wa-Dawrihā fī Nashr al-Thaqāfah al-ʻUmānīyah fī Sharq Ifrīqiyā khilāl ʻAhd al-Sulṭān Barghash ibn Saʻīd (1870-1887) - Khafājī, Aḥmad Bahāʼ ʻAbd al-Razzāq (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
Among the most important marks of advance and of scholarly, intellectual and epistemic refinement is the existence of presses and of a printing movement, and this is what distinguished Omanis in Oman generally and in Zanzibar in particular: the presence of presses had a great effect on the scholarly and cultural renaissance, and the Sultanic Press had a clear role as a contributing factor in it. Hence the pressing need and importance of surveying inductively the efforts of predecessors in publishing the Omani heritage and culture. The Sultanic Press is among the oldest and most venerable Omani government presses in the African East; its founder was Sultan Barghash ibn Saʿīd ibn Sulṭān (1870–1887), who established it in Zanzibar in 1882. At a time when Sultan Barghash devoted his efforts to advancement, this press became the instrument through which Omani culture reached East Africa.
MHF-PRINT2018-016
Keywords: Sultanic Press; Zanzibar; Sultan Barghash; Omani culture; East Africa; Printing history